The Effect of Profitability, Size, Sales Growth, Asset Structur and Liquidity on Capital Structure - Iskandar Yusuf; Zaki Achmad (GREENOMIKA, 2023)
Capital structure is the ratio between the company's long-term debt and equity capital in a company. There are several factors that can affect the capital structure itself, such as profitability, company size, sales growth, asset structure, and liquidity. This study aims to determine the effect of profitability, company size, sales growth, asset structure, and liquidity on the capital structure of the company. The subject of this research is non-financial companies that are included in the LQ45 company sector. The method used is multiple regression analysis method. The samples in this study were 37 companies selected by purpose sampling method. The result of this research is profitability, company size, sales growth and asset structure have no effect on capital structure while liquidity has influence on capital structure.